Korelasi agama dengan modernisasi - Saputra, Moh. Aditya Hadi (Maliki Interdisciplinary Journal, 2025)
Religion today faces various challenges. In the present day religion is forced to continue to survive with the current of modernization. Religion is expected to balance or become a benchmark between moral and human values today. Modernization and religion are interrelated, because people use religion as a guide for life. But in the end it caused a lot of friction. Although there is an impression that religion and modernization are opposites, here I will explain about the relationship between religion and modernization. Because there are several values that attract each other. Indeed, man cannot be separated from religion because man always relies on a higher authority (God) to fulfill his fundamental needs as an intellectual and spiritual person. We can apply the good side of the relationship and avoid the bad effects so as to create a harmonious relationship. With the development of sophisticated technology, religion can remain consistent in existence, while technology can help pay attention to the entire human order to realize progress on the common interest. So religion and modernization must run in balance in order to realize a harmonious life according to the times.